Transient Stability of Multi-Machine Wind Turbine Generators System Connected to the Power Network (University of Khartoum Engineering Journal, 2022)
currently worldwide installed capacity of the network connected wind generators grows rapidly; this rise of integration rate of wind energy could lead to circulation of transient stability and could potentially cause local or system wide blackout. This paper presents a recovery strategy that enables the system of HVDC transmission systems based on voltage source converter, which transmit electrical power from the wind turbines to the power network, to ride-through different positions of ac faults with smallest amount current and voltage stresses on the converter switching devices. Issue such as control strategies for a VSC-HVDC conduction system connecting offshore wind farms to the power network is discussed. The results show that the transient stability study of the system is widely different when the faults occur in neither wind side nor power network side. The DC link voltage behaves similarly to the AC voltage. However when the AC fault occurs in the wind side stations either for ac voltage or DC voltage the system behavior does not return to its normal operation after the fault is cleared. A reduced network model has been implemented in MATLAB/ SIMULINK to assess control performance during the fault.